2016
DOI: 10.14419/ijpt.v4i2.6644
|View full text |Cite
|
Sign up to set email alerts
|

ATM kinase inhibitor KU-55933 contribution in cisplatin mediated HeLa proliferation

Abstract: Several approaches including chemotherapy and radiation therapies are being at the forefront to treat various types of cancer including cervical cancer. However, the success and failure of genotoxic based therapy is attributed to aberrant ability of carcin oma to patch up genomic breaks. Here, we have used cisplatin as a genotoxic drug model and HeLa as in vitro carcinoma model due to less responsiveness and resistance of HeLa against cisplatin. Here, attempts are made to investigate the effects of DNA double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…The DDR is defined as an inherent common feature in both normal and carcinoma in the response to genomic lesions and toxic stress 1214. Both carcinoma and normal cells employ several DNA repair pathways, such as mismatch repair, nucleotide excision repair, base excision repair, homologous recombination, and non-homologous end joining (NHEJ) 1012. DNA DSB is defined as the principle cytotoxic lesion for ionizing radiation, but it can also be generated by genotoxic drugs 914.…”
Section: Introductionmentioning
confidence: 99%
“…The DDR is defined as an inherent common feature in both normal and carcinoma in the response to genomic lesions and toxic stress 1214. Both carcinoma and normal cells employ several DNA repair pathways, such as mismatch repair, nucleotide excision repair, base excision repair, homologous recombination, and non-homologous end joining (NHEJ) 1012. DNA DSB is defined as the principle cytotoxic lesion for ionizing radiation, but it can also be generated by genotoxic drugs 914.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report the clear, reliable and efficient extraction of genotoxic agents in DMSO solvent from chewing tobacco and gutka in an appreciable amount. These obtained DMSO extract from chewing tobacco and gutka was subjected to the standard in vitro DNA damage assay with slight modifications [7]. The analysis of plasmid DNA damage data revealed that DMSO extract of chewing tobacco showed extensive DNA damage up to the ten times dilution of used extract (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The well-known platinum based drug, cisplatin, is being used from decades for carcinoma treatment including cervical cancer. The major issue concerned with cisplatin as a chemotherapeutic option with excessive over dose leading to drug resistance and patients secondary pathophysiological conditions including secondary tumor [2,5,6,10,14,16,22]. The reasons behind cisplatin resistance and efficacy issues may be due to decreased accumulation of drug inside the cell, altered DNA repair or increased efflux of drug [2,10,14,16,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…At global level, cervical cancer is considered as the second most happening cancer types [1]. Chemotherapy is one of the therapies of cancer where the chemical compounds are used as drug to target the genes or proteins [2][3][4][5][6][7][8]. There are several compounds used as anticancer drugs such as alkylating agents including platinum based drugs [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation